Development of military spending determinants in Baltic countries: Empirical analysis - Jakub Odehnal; Jiří Neubauer; Lukáš Dyčka; Tereza Ambler (Economies, 2020)
The article presents the use of the ARDL model to identify military expenditure determinants of the Baltic States (Lithuania, Latvia, and Estonia). Factors influencing military expenditure include the variables characterizing the economic environment of the analyzed countries (GDP per Capita, Government Deficit/Surplus, General Government Gross Debt, Inflation), and the security environment measured by Risk of Foreign Pressures, Risk of Cross-border Conflict, and Democratic Accountability. General conclusions about the analysis of relationships between the military expenditure level and selected economics and security determinants were confirmed in the cases of Government Deficit/Surplus, GDP per Capita and Inflation. The results, therefore, indicate that the military expenditure of Estonia and Lithuania depended on the state budget deficit where military expenditure tended to go down in relation to an increasing deficit within the assessed period. As far as Estonia is concerned, the findings about relationship between the economic position and military expenditure was validated as an increasing economic performance tended to increase military expenditure.
Keywords: C33; H56; E69; 330; military expenditure; ARDL models; Baltic states; security determinants; economic determinants